Activation of ectopic olfactory receptor 544 induces GLP-1 secretion and regulates gut inflammation. (1st January 2021) - Wu, Chunyan; Jeong, Mi-Young; Kim, Jung Yeon; Lee, Giljae; Kim, Ji-Sun; Cheong, Yu Eun; Kang, Hyena; Cho, Chung Hwan; Kim, Jimin; Park, Min Kyung; Shin, You Kyoung; Kim, Kyoung Heon; et al.
ABSTRACT: Olfactory receptors are ectopically expressed in extra-nasal tissues. The gut is constantly exposed to high levels of odorants where ectopic olfactory receptors may play critical roles. Activation of ectopic olfactory receptor 544 (Olfr544) by azelaic acid (AzA), an Olfr544 ligand, reduces adiposity in mice fed a high-fat diet (HFD) by regulating fuel preference to fats. Herein, we investigated the novel function of Olfr544 in the gut. In GLUTag cells, AzA induces the cAMP-PKA-CREB signaling axis and increases the secretion of GLP-1, an enteroendocrine hormone with anti-obesity effects. In wild-type (WT) mice injected AzA, GLP-1 plasma levels were elevated. The induction of GLP-1 secretion was negated in cells with Olfr544 gene knockdown and in Olfr544-deficient mice. Gut microbiome analysis revealed that AzA increased the levels of Bacteroides acidifaciens and microbiota associated with antioxidant pathways. In fecal metabolomics analysis, the levels of succinate and trehalose, metabolites correlated with a lean phenotype, were elevated by AzA. The function of Olfr544 in gut inflammation, a key feature in obesity, was further investigated. In RNA sequencing analysis, AzA suppressed LPS-induced activation of inflammatory pathways and reduced TNF-α and IL-6 expression, thereby improving intestinal permeability. The effects of AzA on the gut metabolome, microbiome, and colon inflammation were abrogated in Olfr544-KO mice. These results collectively demonstrated that activation of Olfr544 by AzA in the gut exerts multiple effects by regulating GLP-1 secretion, gut microbiome and metabolites, and colonic inflammation in anti-obesogenic phenotypes and, thus, may be applied for obesity therapeutics.